2017
DOI: 10.3389/fnins.2017.00151
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Immuno-Communication in Neurodegenerative Diseases

Abstract: Neuro-inflammation is a critical process by which the brain coordinates chemokine-regulated cellular recruitment, cytokine release, and cell-mediated removal of pathogenic material to protect against infection or brain injury. Dysregulation of this immune response is involved in multiple neurodegenerative disorders, however the precise contribution of neuro-inflammation to the exacerbation and progression of these diseases remains unclear. Evidence now suggests that commensal micro-organisms populating the hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 63 publications
(69 reference statements)
0
48
0
Order By: Relevance
“…Also, it has been proposed that the immune response to H. pylori causes apoptosis and neural cell destruction by releasing pro-inflammatory molecules and inducing reactive oxygen metabolites 51 , 62 . There is evidence that H. pylori damages the brain-blood barrier 63 , 64 and the gut metabolites reaches the brain through direct interaction with enteric neurons 42 . Microbial metabolites can also influence the peripheral immune response, which in sequence affects the blood- brain barrier 64 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, it has been proposed that the immune response to H. pylori causes apoptosis and neural cell destruction by releasing pro-inflammatory molecules and inducing reactive oxygen metabolites 51 , 62 . There is evidence that H. pylori damages the brain-blood barrier 63 , 64 and the gut metabolites reaches the brain through direct interaction with enteric neurons 42 . Microbial metabolites can also influence the peripheral immune response, which in sequence affects the blood- brain barrier 64 .…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that H. pylori damages the brain-blood barrier 63 , 64 and the gut metabolites reaches the brain through direct interaction with enteric neurons 42 . Microbial metabolites can also influence the peripheral immune response, which in sequence affects the blood- brain barrier 64 .…”
Section: Discussionmentioning
confidence: 99%
“…20,[29][30][31] Previous studies have suggested that gut microbiota is involved in triggering neuroinflammation in the brain. 18,32 We hypothesized that the observed gut microbiota alteration during AD progression might be associated with neuroinflammation. To test this hypothesis, we evaluated the inflammatory status of Tg mice.…”
Section: Ad Progression Is Associated With the Alteration Of Gut Micrmentioning
confidence: 99%
“…16,17 It remains unknown which types of infiltrated immune cells are functionally involved in AD development. 18,19 The underlying driving force that promotes peripheral immune cells to infiltrate the brain, leading to the enhancement of the residential neuroinflammation, remains obscure. Moreover, as the importance of microbiota metabolites is starting to unveil, it will be imperative to comprehend the specific metabolites that are involved in linking gut microbiota and brain neuroinflammation in AD progression.…”
Section: Introductionmentioning
confidence: 99%
“…A thought-provoking hypothesis is that curli-producing bacteria influence human neurodegenerative and aggregation diseases by nucleating, accelerating or deterring fibrillation of human amyloids. Another mechanism could be affecting the immune system, leading to inflammation and stress that are correlated with neurodegenerative diseases (122,123). Future work is needed to characterize more microbial amyloids at the molecular and atomic level, study their inter-species interactions, and modulate their activities (38).…”
Section: Can Csga Influence Neurodegenerative Diseases?mentioning
confidence: 99%